Design Lesson Planning for English Specific Purpose - Nur Fadilah; Raudhatul Islam; Inayatul Makrufah; Wardatun Navisah; Muhammad Irfan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study explores the lesson planning practices of an English lecturer at Universitas Hafsawaty who teaches English for healthcare students. The findings indicate that the lecturer adopts a contextual and profession-oriented approach, aligning language instruction with medical content and professional communication needs. The lesson plans incorporate materials from health journals, clinical simulations, and academic writing tasks, aiming to enhance both linguistic proficiency and professional relevance. Instructional strategies such as scaffolded learning and multimodal media use are applied to accommodate students’ diverse English proficiency levels. The discussion highlights the integration of English for Specific Purposes (ESP) and Content and Language Integrated Learning (CLIL) frameworks, emphasizing experiential learning and interdisciplinary collaboration. Overall, the study underscores the importance of context-driven lesson planning and the need for institutional support in developing English instruction tailored to professional domains.